1999
DOI: 10.1002/(sici)1098-1071(1999)10:3<213::aid-hc7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

C-phosphorylation of n-methylpyrrole

Abstract: The phosphorylation of N‐methylpyrrole with phosphorus (III) halides has been studied. Migration of the dibromophosphino group from the second to the third position of N‐methylpyrrole, leading to the 3‐dibromophosphine, has been found. Methods for the synthesis of 2,4‐bisphosphorylated pyrroles have been developed. © 1999 John Wiley & Sons, Inc. Heteroatom Chem 10:213–221, 1999

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Zipse and co-workers studied substituents effects on the methyl cation affinity (MCA) of phosphines and showed that small N -heterocyclic substituents such as the pyrrolyl group lead to phosphines with remarkably high affinity to carbon electrophiles. , In the series of pyrrolylphosphines, the most effective electron-donating effects were observed when the phosphorus atom is connected to the C3 position of the pyrrole ring, while C2-connected pyrrolyl and phenyl substituents are comparable in this respect (Figure ). Tris­( N -pyrrolyl)­phosphine , is a weak electron donor and good π-acceptor ligand, which has been successfully applied in hydroformylation reactions. The C2-connected structural isomer, tris­(1-methylpyrrol-2-yl)­phosphine, was first reported in 1974, followed by several derivatives of (1-methylpyrrol-2-yl)­phosphines. Yet, the properties of these phosphines have barely been investigated. , Among them, the cataCXium ligands represent a prominent class of N -arylated pyrrolylphosphines, which have been used in Suzuki cross-coupling reactions . Few reports exist about C3-bound pyrrolylphosphines. ,, In fact, the only representative with three pyrrolyl groups, tris­(1- tert -butylpyrrol-3-yl)­phosphine, has been generated in situ but was not isolated, and the electronic properties were not investigated .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zipse and co-workers studied substituents effects on the methyl cation affinity (MCA) of phosphines and showed that small N -heterocyclic substituents such as the pyrrolyl group lead to phosphines with remarkably high affinity to carbon electrophiles. , In the series of pyrrolylphosphines, the most effective electron-donating effects were observed when the phosphorus atom is connected to the C3 position of the pyrrole ring, while C2-connected pyrrolyl and phenyl substituents are comparable in this respect (Figure ). Tris­( N -pyrrolyl)­phosphine , is a weak electron donor and good π-acceptor ligand, which has been successfully applied in hydroformylation reactions. The C2-connected structural isomer, tris­(1-methylpyrrol-2-yl)­phosphine, was first reported in 1974, followed by several derivatives of (1-methylpyrrol-2-yl)­phosphines. Yet, the properties of these phosphines have barely been investigated. , Among them, the cataCXium ligands represent a prominent class of N -arylated pyrrolylphosphines, which have been used in Suzuki cross-coupling reactions . Few reports exist about C3-bound pyrrolylphosphines. ,, In fact, the only representative with three pyrrolyl groups, tris­(1- tert -butylpyrrol-3-yl)­phosphine, has been generated in situ but was not isolated, and the electronic properties were not investigated .…”
Section: Introductionmentioning
confidence: 99%
“…Tris­( N -pyrrolyl)­phosphine , is a weak electron donor and good π-acceptor ligand, which has been successfully applied in hydroformylation reactions. The C2-connected structural isomer, tris­(1-methylpyrrol-2-yl)­phosphine, was first reported in 1974, followed by several derivatives of (1-methylpyrrol-2-yl)­phosphines. Yet, the properties of these phosphines have barely been investigated. , Among them, the cataCXium ligands represent a prominent class of N -arylated pyrrolylphosphines, which have been used in Suzuki cross-coupling reactions . Few reports exist about C3-bound pyrrolylphosphines. ,, In fact, the only representative with three pyrrolyl groups, tris­(1- tert -butylpyrrol-3-yl)­phosphine, has been generated in situ but was not isolated, and the electronic properties were not investigated . Note that the structurally related (indol-3-yl)­phosphines are powerful ligands for Pd-catalyzed cross-coupling reactions. , Herein, we report the synthesis and properties of a series of (1,2,5-trimethylpyrrolyl)­phosphines that, consistent with Zipse’s prediction, are strongly electron-donating arylphosphines.…”
Section: Introductionmentioning
confidence: 99%
“…A C-5 methyl group should prevent migration of a phosphine group between C-2 and C-3, a process that has been widely observed for other pyrazole derivatives. 36,37 In addition, some analogues of 2-aminobiphenyl have been employed as pesticidal agents.…”
Section: Resultsmentioning
confidence: 99%
“…1 of biologically active compounds such as antibacterial [1], anti-inflammatory [2,3], analgesic [3], antitumor [4,5], anticancer activities [6] etc., and in organic synthesis is well documented [7][8][9][10]. The synthetic access to various C-phosphorylated five-membered N-heterocycles via electrophilic phosphorylation with P(III) halides is known [10][11][12][13]. The coordination of phosphanes to metals and the spectroscopic properties of phosphorus are two important aspects of this chemistry [14].…”
Section: Introductionmentioning
confidence: 99%